Contagion - Robin F. Cook (U.S.A Berkley Books, 1995)
Contagion is a terrifying cautionary tale for the millennium as a deadly epidemic is spread not merely by microbes$1 (Bbut by sabotage... s
Keywords: Mystery -- Mystery; Suspense -- Suspense